Quality assessment on economic evaluation studies for different immuni-zation strategies of varicella vaccines in 2004 - 2021 - Bai-chu GUAN; Yi-han LU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo conduct a quality assessment on studies for economic evaluation of different immunization strategies of varicella vaccines in February 2004 - November 2021 and to provide references for the decision-making of varicella vaccine immunization in China. MethodsRelevant studies published in Chinese and English during February 2004 - November 2021 were retrieved using terms of varicella vaccine, economic evaluation, cost, cost-benefit, cost-effect and cost-utility through searching China National Knowledge Infrastructure, Wanfang Data Knowledge Service Platform, Vip Database , Web of Science, PubMed, EMBASE, Medline, Scopus, and Google Scholar. Related information were extracted from the studies screened-out according to World Health Organization's Guideline for Standardized Economic Evaluation on Immunization Programmes and the Quality of Health Economic Studies (QHES) instrument was utilized to evaluate the quality of the studies. ResultsThe analysis on 13 studies finally included (4 published in Chinese and 9 in English) showed that compared to no vaccination, both one-dose and two-doses vaccination strategy were cost-effective. Contrasting to the results of analysis on one-dose vaccination strategy, consistent conclusion was reached for the cost-effectiveness of two-doses strategy, although some studies demonstrated that the cost-effectiveness of two-doses vaccination increased over time. ConclusionMore studies should be conducted on comparison of economic cost-effectiveness between one-dose and two-doses vaccination strategy of varicella vaccine.